2010
DOI: 10.3109/14767058.2010.501123
|View full text |Cite
|
Sign up to set email alerts
|

Flexible fiberoptic bronchoscopy – a bedside technique for neonatologists

Abstract: FFB is a useful and safe procedure that belongs in the neonatologists' armamentarium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 19 publications
7
20
0
Order By: Relevance
“…The populations with the highest diagnostic yield of FFB were patients with extubation failure, patients with CHD, patients with hemoptysis, and patients undergoing ECLS. In patients with extubation failure, FFB identified a cause, such as mucus plugs, laryngotracheomalacia, laryngeal trauma/edema or compression, in 69.9% (range 50%-90.5%; 51/73) [3,[16][17][18][19][20][21]24,27,31,32] .…”
Section: Diagnostic Yield Of Ffbmentioning
confidence: 99%
See 2 more Smart Citations
“…The populations with the highest diagnostic yield of FFB were patients with extubation failure, patients with CHD, patients with hemoptysis, and patients undergoing ECLS. In patients with extubation failure, FFB identified a cause, such as mucus plugs, laryngotracheomalacia, laryngeal trauma/edema or compression, in 69.9% (range 50%-90.5%; 51/73) [3,[16][17][18][19][20][21]24,27,31,32] .…”
Section: Diagnostic Yield Of Ffbmentioning
confidence: 99%
“…De Blic et al [4] reported that in children with CHD, FFB findings of external compression of the airways by cardiovascular anomalies prompted earlier cardiac surgery in 50% (5/10) [4] . Twenty-one studies reported an overall diagnostic yield of 82% using FFB (range 45.2%-100%; 3791/4 622) [3][4][5][14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . [27] , 2011 [20,24,31] .…”
Section: Diagnostic Yield Of Ffbmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultra-thin bronchoscopes offers new diagnostic opportunities, particularly to neonatologists [5]. Furthermore, ultra-thin bronchoscopes are of limited diagnostic value when excessive bronchial secretions obstruct the view of the working field because of the abscence of the suction channel.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of disease ranges from airway disease associated with congenital heart disease, acquired tracheabronchomalacia requiring long-term ventilation to subglottic stenosis requiring tracheostomy. Fiber-optic bronchoscopy in the ICU is required to assess the airways of these neonates and children to assure correct management [15][16][17][18][19][20]. Performing a bronchoscopy safely in the ICU requires a different skill set as in the ICU there is an increased risk of developing complications and managing them in an unfamiliar environment.…”
Section: Indications For Bronchoscopy In Children In Lmicmentioning
confidence: 99%